FIRST FIND OF NATURAL COPPER- AND MAGNESIUM-BEARING GIBBSITE - Slukin A.D.; Tsimlyanskaya L.S. (My University, 1989)
In 1978, in Precambrian metamorphosed bauxites of the Alag Uula deposit, we found a mineral identified as gibbsite high in copper and magnesium. This deposit is in western Mongolia in the eastern part of the Yihe Daribi Range, which consists of Proterozoic and Vendian-Cambrian deposits, intruded by granitoids and the large Alag Uula pluton. The unique composition of such gibbsite reflects the genetic particulars of the deposit studied. The magnesium in gibbsite was derived from chlorite and spinel, as well as from ultramafic rocks and their hydrothermal and supergene alteration products - talc, magnesite and nontronite. The Cu, Ni and Co were derived from serpentine and sulfides in these ultramafic rocks. Corundum, diaspore, spinel and chlorite were disolved during weathering; alumina went into solution and was carried away by infiltrating water or deposited on the same minerals, in pores and in fraction as gels. The latter also coprecipitated and sorbed Mg, Co, Cu, Si, Ca, Ni, Na and other elements.
Keywords: Vendian; Proterozoic; Precambrian; Cambrian; Precambrian::Proterozoic::Neoproterozoic::Vendian; Precambrian::Proterozoic; Precambrian; Paleozoic::Cambrian; Палеозой::Кембрийская; Докембрий; Докембрий::Протерозой::Неопротерозойская::Вендский; Докембрий::Протерозой